Effectiveness of Group Guidance with Symbolic Modelling in Reducing Verbal Aggression among Junior High School Students - Nur Halima Tusyadiah; Saiful Akhyar Lubis (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study is a quantitative research employing a quasi-experimental model with a non-equivalent control group pretest-posttest design, which compares the results before and after the intervention between two different groups. The population of this study consisted of seventh-grade students at MTs Swasta Darul Ulum Budi Agung who were identified as having verbal aggression behaviour, with a sample of 16 students divided into experimental and control groups, each consisting of eight students, selected through purposive sampling. The instrument used to measure students’ verbal aggression behaviour was a questionnaire developed based on Kartini Kartono’s framework, which had been tested for validity and reliability. Data analysis was conducted using the paired sample t-test and the independent sample t-test. The findings revealed a significant decrease in students’ verbal aggression behaviour in the experimental group, with the average pretest score increasing from 53.38 (low category) to 95.63 (high category) in the posttest. This was supported by a significance value of 0.000 (p < 0.05), indicating the effectiveness of the intervention in reducing students’ verbal aggression behaviour. Therefore, it can be concluded that group counselling services with symbolic modelling techniques are effective in reducing verbal aggression among junior high school students, and it is recommended that they be implemented as a preventive strategy in school counselling services.